2017
DOI: 10.1111/ajpy.12152
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coping and resilience on anxiety among older Australians

Abstract: Objective: This study aims to explore the relationships between various coping types, resilience, and anxiety among older Australians. Particular attention is paid to whether resilience moderates coping's effect on anxiety. Method: A total of 324 Australians aged between 55 and 90 (M = 66.7, SD = 8.6) were surveyed as part of the study. Moderation was assessed using structural equation modelling and plots of simple slopes. Results: Significant negative correlations were detected between anxiety and both proact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…One explanation for this finding might be that the relation between coping and anxiety is conditional. It would be affected by some moderators (Li and Miller, 2017 ), which requires additional research to achieve a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this finding might be that the relation between coping and anxiety is conditional. It would be affected by some moderators (Li and Miller, 2017 ), which requires additional research to achieve a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…A resilient healthcare worker is capable of combatting stress through enhanced recovery in response to stressful stimuli ( Squiers et al, 2017 ). Instead of passively enduring stress, a resilient individual can bounce back and thrive in the face of adversity ( Li and Miller, 2017 ), which may support healthcare professionals to cope with work-related stress and traumas that possibly lead to BO and STS.…”
Section: Discussionmentioning
confidence: 99%
“…In past research, resilience has demonstrated a positive correlation with reflective, proactive, preventative, and problem-oriented coping strategies, identifying such coping strategies as beneficial components to resilience [33,34]. Thus, school teachers who possess resilience may better adapt to challenging occupational stressors, which help to reduce mental health issues such as depression and anxiety [18,59,60].…”
Section: Discussionmentioning
confidence: 99%